Exploitation of the Ugi–Joullié reaction in drug discovery and development. (3rd July 2019) - Gazzotti, Stefano; Rainoldi, Giulia; Silvani, Alessandra
ABSTRACT: Introduction : Multicomponent reactions are paramount in drug discovery for their ability to achieve high levels of diversity within the chemical space, generating complex structures from simple building blocks. Among them, the isocyanide-based Ugi-Joulliè reaction is particularly suited for the rapid synthesis of peptidomimetics and nitrogen-containing compounds. Areas covered : The latest achievements in drug discovery and synthetic chemistry regarding the application of the Ugi-Joulliè reaction in the field of natural compounds, peptidomimetics and small molecules, are reported in this article. All relevant literature was disclosed applying most common web-based literature searching tools, namely Web of Science, PubMed, SciFinder and Google Scholar. Expert opinion : The Ugi-Joulliè reaction represents an extremely versatile and simple synthetic methodology, useful for designing efficiently new molecular frameworks. Particularly relevant to drug discovery is the Ugi-Joulliè-based synthesis of conformationally constrained peptidomimetics and antibacterial depsipeptides. On the other hand, the many syntheses of new, nitrogen-containing heterocycles are not always followed by biological evaluation, losing opportunities for the disclosure of unprecedented lead compounds.